Regioselectivity in C–H activation: reagent control in cyclometallation of 2-(1-naphthyl)-pyridine. Issue 2 (24th November 2015) - Kondrashov, Mikhail; Provost, David; Wendt, Ola F.
Abstract : The choice of metallating agent completely reverses the regioselectivity in cyclometallation of 2-(1-naphthyl)-pyridine. Abstract : 2-(1-Naphthyl)-pyridine (1 ) possesses sp 2 C–H bonds in both the γ- and δ-positions and is therefore a suitable substrate for studying the cyclometallation selectivity with different reagents and conditions. Such selectivity studies are reported. Based on deuterium-exchange experiments it is concluded that cycloruthenation with RuCl2 ( p -cymene) dimer is reversible with kinetic and thermodynamic preference for γ-substitution. Electrophilic cycloborylation, on the other hand, shows unusual δ-substitution. The previously published cyclopalladation and cycloauration of the substrate was studied in detail and was shown to be irreversible; they proceed under kinetic control and give γ- and δ-substitution for palladium and gold, respectively.